Factors that Associated with the Practice of Exclusive Breastfeeding - Nafiatus Sintya Deviatin (LPPM STIKES KENDAL, 2021)
The first thousand days of life (1000 HPK) Movement is a national movement carried out by the Government of Indonesia to accelerate the improvement of nutrition in the first thousand days of child’s life. One of the problems with child nutrition is stunting. One of the factors that contribute to stunting is exclusive breastfeeding. Wonokusumo village is one of the urban villages in Surabaya City that has low exclusive breastfeeding coverage, which is 57.07% in 2018. This study aims to determine the factors associated with the practice of exclusive breastfeeding in the baby under two years in the region of Wonokusumo Primary Health Center in Surabaya City. This study is an analytic observational study using a cross-sectional design. The sampling technique uses a non-probability sampling technique, namely the consecutive sampling method. The entire population was sampled in the study, a total of 56 mothers of baby 0-23 months. The research data is secondary data from the results of the fieldwork practice of students of the Faculty of Public Health, Airlangga University. The research data were analyzed using the chi-square test through the SPSs application. Research results show that there is no relationship between mother’s age, mother’s education level, mother’s occupation, history of infectious diseases, and the activeness of attending an integrated service post (Posyandu) with exclusive breastfeeding practices (P value> 0.05).